“Manchas de voz”, de Juan Vicente Piqueras: metapoesía y pre-verbal - Alessandro Mistrorigo (Caracteres: Estudios Culturales y Críticos de la Esfera Digital, 2016)
Since writing and human voice are media, which the poets always worked with, interactions and interferences created between the text and the author reading it aloud fall within the reach of the intermedial phenomena. Thanks to the specific case of the poem “Manchas de voz” by Spanish poet Juan Vicente Piqueras and the recording that he realised under the Phonodia project, this article shows the shift of status that concerns, on the one hand, the figure of reader and, on the other hand, the figure of the author in relation to his own voice as a mean.